Analysis of Factors Contributing to Impulse Buying Behavior of E-Commerce Users - Ronaldo Yolanda Putra; Syifa Nurul Fadillah; Annisa Afifah Nugroho; Ifta Firdausa Nuzula (Journal of Management Studies and Development, 2022)
Ease of accessing the internet and information technology triggers impulsive buying behavior through increased accessibility to products and services that facilitate the buying process. Through internet facilities by browsing, consumers can feel like window shopping in a mall. This study focuses on the Java-Bali area which is a strategic location in access to products. Data were collected from 273 respondents of E-commerce users using a survey method. Structural Equation Modeling (SEM) modeling technique with SmartPLS 3.0 software. The results show that e-commerce browsing and the big five models have a significant effect on urge to purchase and impulse purchase. E-commerce usage intensity and urge to purchase have no effect on impulse purchases and the results of the mediation role test of urge to purchase have no effect on e-commerce browsing, e-commerce usage intensity, and the big five model on impulse purchases.